Chemical profiling of Phlomis thapsoides (Lamiaceae) and in vitro testing of its biological activities - Sobeh, Mansour; Mamadalieva, Nilufar Z.; Mohamed, Tamer; Krstin, Sonja; Youssef, Fadia S.; Ashour, Mohamed L.; Azimova, Shahnoz S.; Wink, Michael (Medicinal chemistry research, 2016)
A phytochemical study of Phlomis thapsoides (Lamiaceae) resulted in the isolation of one new compound, 6,10,17-trimethyl-2-octadecanone, and three known compounds (sitosterol-3-O-β-glucoside, and the iridoid glucosides ipolamiide and lamiide). The structures of the isolated compounds were elucidated using mass spectrometry, 1D/2D NMR spectroscopy experiments in comparison with published data. The chemical composition of the essential oil obtained from aerial parts of P. thapsoides was determined by gas liquid chromatography and gas liquid chromatography-mass spectroscopy. The main volatile constituents were phenylethyl alcohol (6.81 %), trans-3-hexenol (5.55 %), 1-octen-3-ol (5.10 %), α-cadinol (4.92 %), and α-muurolol (4.67 %). The antioxidant activity of the extracts was evaluated by three methods: 1,1-diphenyl-2-picrylhydrazyl free radical scavenging activity, 2,2′-azinobis-[3-ethylbenzthiazoline-6-sulfonic acid] and ferric reducing antioxidant power assay along with the determination of total phenolic content. Although the ethyl acetate extract contained 362.06 mg of gallic acid equivalents, the antioxidant activities, as revealed by 1,1-diphenyl-2-picrylhydrazyl, 2,2′-azinobis-[3-ethylbenzthiazoline-6-sulfonic acid] and ferric reducing antioxidant power assays, were of medium strength (IC50 of 73.08 ± 3.18, 9.48 ± 0.71 µg/mL and 9.33 ± 0.17 mM of FeSO4 equivalents, respectively). Only lamiide inhibited soybean 5-lipoxygenase with an IC50 value of 72.92 µg/mL in vitro. In-silico molecular modeling studies on 5-lipoxygenase and human 5-lipoxygenase-activating protein were used to evaluate the potential anti-inflammatory activity. Sitosterol-3-O-β-glucoside followed by the iridoid glucoside lamiide exhibited the highest inhibition of 5-lipoxygenase whereas the new compound 6,10,17-trimethyl-2-octadecanone and sitosterol-3-O-β-glucoside exhibited the highest inhibition of 5-lipoxygenase-activating protein as evidenced from their higher fitting scores. The cytotoxicity of the plant extracts and lamiide against Caco2 and HepG-2 cancer cells resulted in IC50 values of >100 µg/mL indicating a low cytotoxicity.
Gesehen am 02.02.2017